A standardized polyphenol mixture extracted from poplar-type propolis for remission of symptoms of uncomplicated upper respiratory tract infection (URTI): A monocentric, randomized, double-blind, placebo-controlled clinical trial - Esposito, Cristina; Garzarella, Emanuele Ugo; Bocchino, Bruno; D'Avino, Maria; Caruso, Giuseppe; Buonomo, Antonio Riccardo; Sacchi, Roberto; Galeotti, Fabio; Tenore, Gian Carlo; Zaccaria, Vincenzo; Daglia, Maria (Phytomedicine (Stuttgart), 2021)
The most common symptoms of mild upper respiratory tract infections (URTIs) are sore throat, muffled dysphonia, and swelling and redness of the throat, which result from the inflammation process following acute bacterial or viral infection. As propolis is a natural resinous substance traditionally used to maintain oral cavity and upper respiratory tract health due to its antimicrobial and anti-inflammatory properties, the aim of this study is to evaluate the efficacy of an oral spray based on poplar-type propolis extract with a known and standardized polyphenol content, on the remission of the symptoms associated with mild uncomplicated URTIs. A monocentric, randomized, double-blind, placebo-controlled clinical trial was performed. This study was conducted in 122 healthy adults who had perceived mild upper respiratory tract infections. Participants, randomly assigned to receive either propolis oral spray (N = 58) or placebo (N = 64), underwent four visits (baseline = t0, after 3 days = t1 and after 5 days = t2 and after a follow-up of 15 days = t3) in an outpatient setting. Propolis oral spray total polyphenol content was 15 mg/ml. The dosage was 2-4 sprays three times/day (corresponding to 12-24 mg of polyphenols/day), for five days. The duration of the study was 8 weeks. After 3 days of treatment, 83% of subjects treated with propolis oral spray had remission of symptoms, while 72% of subjects in the placebo group had at least one remaining symptom. After five days, all subjects had recovered from all symptoms. This means that resolution from mild uncomplicated URTIs took place two days earlier, instead of taking place in five days as recorded in the control group. There was no relationship between the ingestion of propolis oral spray or placebo and adverse reactions. Propolis oral spray can be used to improve both bacterial and viral uncomplicated URTI symptoms in a smaller number of days without the use of pharmacological treatment, leading to a prompt symptom resolution. [Display omitted]